Cyclic fatigue resistance and shaping ability of heat-treated nickel-titanium instruments after repeated use - TÜRKAYDIN, DİLEK; GÖKER KAMALI, SELİN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Aims: To evaluate the effect of multiple-use and sterilization on cyclic fatigue and shaping ability of heat-treated nickel-titanium (NiTi) rotary instruments. Methods: A total of 120 acrylic blocks with S-shaped canals were photographed and prepared by HyFlex CM, ProTaper Next, and Twisted File. Ten new sets of each rotary instruments were used for four times. The autoclaving process was repeated after each use. Pre- and post instrumentation images were superimposed. The amount of resin removal and canal transportation by each system was measured in eleven different points. Instruments were subsequently subjected to a cyclic fatigue test in a double-curved artificial canal. The means and standard deviations of the number of cycles to failure (NCF) were calculated and statistically analyzed (P < 0.05). Results: No fractures occurred during the shaping of the simulated canals. The ProTaper Next removed the greatest amount of resin, whereas the Twisted File had the lowest values at all levels. Repeated clinical use and sterilization resulted in a decrease in the resin removal at most levels in Twisted File and ProTaper Next. In terms of canal transportation, an increase in a limited number of levels was detected after repeated use of all rotary files. Twisted File had the greatest cyclic fatigue resistance, followed by HyFlex CM and ProTaper Next (P < 0.05). Conclusions: The effects of repeated use and autoclaving on the cyclic fatigue resistance of HyFlex CM, ProTaper Next, and Twisted File were not significant. Canal transportation increased mostly in the apical region. The amount of resin removal decreased as the number of use increased for ProTaper Next and Twisted File instruments.
Keywords: Cyclic fatigue; multiple-use; repeated use; shaping ability; transportation